A positive electrode active material, a preparation method thereof, a positive electrode sheet, and a lithium ion battery

CN122619779BActive Publication Date: 2026-10-20JINLONGYU NEW ENERGY (SHENZHEN) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611114750.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-20
Estimated Expiration
2046-07-27

AI Technical Summary

Technical Problem

固相法的工艺简单,但产物粒径分布不均,元素混合均匀性差,电化学性能不理想

Benefits of technology

本发明的正极活性材料包括磷酸锰铁锂内核和导电包覆层磷酸锰铁锂内核由草酸盐核心、碳酸盐中间层和磷酸盐壳层三层结构的磷酸锰铁锂前驱体转化获得,且前驱体中的铁和锰元素呈现梯度分布,通过对磷酸锰铁锂前驱体的结构以及元素成分的调控,使获得的正极活性材料具有堆积紧密、孔隙少、压实密度高的特点,且能使得正极活性材料构成三维互联的传输网络,以加速锂离子扩散与迁移、降低阻抗和改善高倍率放电性能,有利于提升电池的首次循环效率与循环稳定性。此外,通过前驱体中浓度梯度的高锰核心和富铁外壳的结构设计,使得正极材料实现高高锰核心提供高容量以及富铁外壳稳定结构的效果,能有效抑制锰溶出与结构畸变,进一步提升循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122619779B_ABST
    Figure CN122619779B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of positive electrode active material and its preparation method, positive pole piece and lithium ion battery, belong to electrochemical energy storage technical field.The positive electrode active material of the present application includes lithium manganese iron phosphate core and the conductive coating layer being arranged on the surface of lithium manganese iron phosphate core;The precursor of lithium manganese iron phosphate core includes oxalate core, carbonate intermediate layer being arranged on the surface of oxalate core and phosphate shell being arranged on the outer surface of carbonate intermediate layer;In precursor, the content of manganese gradually decreases from core to shell, and the content of iron gradually increases from core to shell.The present application is used in lithium ion battery by the regulation of the microstructure of positive electrode active material, so that the first cycle efficiency and cycle stability of battery are significantly improved, and the dissolution of manganese and structural distortion can be effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a positive electrode active material and its preparation method, a positive electrode sheet, and a lithium-ion battery. Background Technology

[0002] Lithium manganese iron phosphate (LMFP), as a cathode material with an olivine structure, has attracted widespread attention due to its high safety, low cost, environmental friendliness, and higher voltage platform and energy density compared to lithium iron phosphate (LFP). However, the introduction of manganese into LMFP makes it prone to Mn oxidation during charge and discharge. 2+ Transform into Mn 3+ The John-Teller effect causes battery volume expansion, leading to irreversible structural changes and side reactions, resulting in decreased cycle stability. Simultaneously, the dissolution of manganese in LMFP further reduces the material's specific capacity, affecting the battery's long-term cycle performance. The crystal structure of LMFP results in low electronic conductivity, leading to significant polarization during charge and discharge, impacting the battery's rate performance and cycle stability. It also increases the difficulty of lithium-ion insertion / deintercalation, further limiting the application of LMFP in high-rate charge / discharge scenarios. Furthermore, the low compaction density of LMFP affects the battery's energy density, further restricting its application in high-energy-density demand scenarios.

[0003] Currently, the main methods for preparing LMFP include high-temperature solid-state methods, sol-gel methods, and hydrothermal or solvothermal methods. Solid-state methods are simple, but the product has uneven particle size distribution, poor elemental mixing uniformity, and unsatisfactory electrochemical performance. Liquid-phase methods (such as co-precipitation) can improve the uniformity of elemental distribution, but the precursors usually have relatively simple chemical compositions and crystal structures, limiting the ability to finely control the microstructure of the final product. Furthermore, manganese and iron elements may still segregate during the subsequent high-temperature solid-state reaction, affecting the uniformity and stability of the material properties.

[0004] Therefore, there is an urgent need to develop a technical solution that can improve the electronic conductivity, ion diffusion rate and structural stability of LMFP materials. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a positive electrode active material, its preparation method, a positive electrode sheet, and a lithium-ion battery. The positive electrode active material provided by this invention, while achieving controllable spatial distribution of manganese and iron elements, simultaneously improves electronic conductivity, ion diffusion rate, and structural stability, thereby enhancing battery performance.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing a positive electrode active material, comprising the following steps: S1. Under an inert gas atmosphere, oxalic acid source and solution A1 are reacted at pH-1 to obtain a system containing oxalate crystal nuclei. S2. Maintaining an inert gas atmosphere, add solution A2 and a carbonic acid source to the system containing oxalate crystal nuclei, and react at pH-2 to obtain a system containing carbonate-coated oxalate crystal nuclei. S3. Maintaining an inert gas atmosphere, add solution A3 and a phosphate source to the system containing carbonate-coated oxalate crystal nuclei, and react at pH -3. After solid-liquid separation, washing, and drying, a solid precursor is obtained. The precursor includes an oxalate core, a carbonate intermediate layer disposed on the surface of the oxalate core, and a phosphate shell disposed on the outer surface of the carbonate intermediate layer. The precursor contains manganese and iron elements, and the precursor satisfies the following relationship: M1 > M2 > M3, N1 < N2 < N3, where M1, M2, and M3 are the percentages of the molar amount of manganese in the oxalate core, carbonate intermediate layer, and phosphate shell relative to the total molar amount of manganese and iron, respectively; and N1, N2, and N3 are the percentages of the molar amount of iron in the oxalate core, carbonate intermediate layer, and phosphate shell relative to the total molar amount of manganese and iron, respectively. M1 > M2 > M3 indicates that the manganese content in the precursor gradually decreases from the oxalate core to the phosphate shell; N1 < N2 < N3 indicates that the iron content in the precursor gradually increases from the oxalate core to the phosphate shell. The core of the positive electrode active material in this application is lithium manganese iron phosphate (LMFP), which is obtained by conversion of a three-layer precursor. In this precursor, the manganese and iron elements exhibit a gradient controllable spatial distribution from the core center to the surface at the nanometer to submicrometer scale. S4. The precursor, lithium source, phosphorus source, dopant, composite carbon source, ion conductor and organic solution are mixed and then subjected to drying, pre-sintering under an inert atmosphere and high-temperature sintering in sequence to obtain the positive electrode active material. In S1 to S3, solution A1, solution A2 and solution A3 include a manganese source and / or an iron source.

[0007] The preparation method provided by this invention achieves precise, layer-by-layer control of the precursor's microstructure and chemical composition in a liquid environment through a three-step continuous precipitation preparation process with independently adjustable parameters. Furthermore, through a two-step sintering process of low-temperature pre-sintering and high-temperature crystallization, it ensures that the precursor with a three-layer structure fully reacts with the lithium, phosphorus, and carbon sources and achieves uniform carbon coating. The pre-sintering process causes each layer of the precursor to gradually decompose and transform, avoiding particle melting or elemental agglomeration caused by direct high temperature, which is beneficial for forming a final product with a uniform particle size distribution.

[0008] Its core component is mainly oxalate precipitate with fine grains, which can achieve uniform mixing of manganese and iron at the atomic level, laying the foundation for the uniform distribution of Mn and Fe in the core. At the same time, the oxalate particles are tightly packed, which helps to increase the tap density of the precursor, so as to achieve the purpose of forming a final product with tight interparticle packing, fewer pores and higher compaction density. Furthermore, the oxalate decomposition temperature is relatively low, which helps the diffusion and reaction of active ions in the subsequent sintering process.

[0009] The intermediate layer is mainly composed of carbonate precipitates, whose chemical properties are between those of the oxalate core and the phosphate shell. This helps to alleviate stress or interface defects caused by the difference in physical properties between the core and the shell. Furthermore, the carbonate produces gas (CO2) during subsequent decomposition, which can leave appropriate nanopores or channels inside the particles. Combined with the carbon layer, these nanopores or channels together form a three-dimensional interconnected ion and electron transport network, allowing lithium ions to diffuse rapidly through the internal micropores / channels and migrate along the surface of the carbon coating layer, thus improving the high-rate discharge performance of the material.

[0010] The shell is mainly composed of phosphate precipitate, which has similar anionic groups (PO4) to the product LMFP. 3- In the subsequent solid-state reaction with the lithium source, it can react preferentially and gradually, reducing particle surface defects caused by violent reactions, forming a dense and stable surface interface, realizing LMFP with a core surface with good crystallinity, reducing the charge transfer impedance at the electrode / electrolyte interface, and helping to improve the first cycle efficiency and cycle stability of the battery.

[0011] This invention designs a three-layer precursor structure for the aforementioned LMFP core and precisely controls the manganese content in the precursor core to decrease from the core to the shell, while the iron content increases from the core to the shell. This results in the core of the final positive electrode active material having a high manganese content center, providing a stable structure with a high-capacity, iron-rich shell. This effectively inhibits manganese leaching and structural distortion, and improves cycle stability.

[0012] Preferably, M1 is 80%-100%, for example, it can be a range of one or any two of 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 100%.

[0013] Preferably, N1 is 0%-20%, for example, it can be a range of one or any two of 0%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%.

[0014] Preferably, M2 is 50%-80%, for example, it can be a range of one or any two of 50%, 53%, 56%, 59%, 62%, 65%, 68%, 71%, 74%, 77%, 80%.

[0015] Preferably, N2 is 20%-50%, for example, it can be a range of one or any two of 20%, 23%, 26%, 29%, 32%, 35%, 38%, 41%, 44%, 47%, 50%.

[0016] Preferably, M3 is 0%-40%, for example, it can be a range of one or any two of 0%, 4%, 8%, 12%, 16%, 20%, 24%, 28%, 32%, 36%, and 40%.

[0017] Preferably, N3 is 60%-100%, for example, it can be a range of one or any two of 60%, 64%, 68%, 72%, 76%, 80%, 84%, 88%, 92%, 96%, 100%.

[0018] Preferably, in the reaction of S1, pH-1 is controlled to be 1-3, for example, it can be a range of one or any two of 1, 1.5, 2, 2.5, and 3.

[0019] Preferably, in step S1, the reaction time is 0.5-6 hours.

[0020] Preferably, in S1, the molar ratio of manganese to iron in solution A1 is (7-10):(0-3), for example, it can be one or any two of the following: 7:3, 7.5:2.5, 8:2, 8.5:1.5, 9:1, 9.5:0.5, 10:0.

[0021] Preferably, the pH-2 in the reaction of S2 is controlled to be 3-5.5, for example, it can be one or any two of the values ​​of 3, 3.5, 4, 4.5, 5, 5.5.

[0022] Preferably, in step S2, the reaction time is 0.5-6 hours.

[0023] Preferably, in S2, the molar ratio of manganese to iron in solution A2 is (3-7):(3-7), for example, it can be one or any two of the following: 3:7, 3.5:6.5, 4:6, 4.5:5.5, 5:5, 5.5:4.5, 6:4, 6.5:3.5, 7:3.

[0024] Preferably, the pH-3 in the reaction of S3 is controlled to be 5.5-7, for example, it can be one or any two of 5.5, 6, 6.5, and 7.

[0025] Preferably, in step S3, the reaction time is 2-24 hours.

[0026] Preferably, in S3, the molar ratio of manganese to iron in solution A3 is (0-3):(7-10), for example, it can be one or any two of the following: 0:10, 0.5:9.5, 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7.

[0027] Preferably, in S1 to S3, the inert atmosphere is at least one of nitrogen, argon, and hydrogen.

[0028] Preferably, in step S4, the molar ratio of manganese to iron in the precursor is (5-8):(2-5), for example, it can be one of 5:5, 6:4, 7:3, 8:2 or any two of them.

[0029] Preferably, in step S4, the composite carbon source includes at least two of the following: sucrose, glucose, citric acid, fructose, starch, maltose, cellulose, dextrin, lactose, oxalic acid, polypropylene, polyvinylpyrrolidone, polyethylene glycol, carbon black, carbon nanotubes, and graphene.

[0030] Preferably, in step S4, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate.

[0031] Preferably, in step S4, the phosphorus source includes at least one of phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.

[0032] Preferably, in step S4, the dopant includes at least one of oxides, oxalates, and carbonates of M, wherein M is at least one of Mg, Al, Ca, Ti, V, Cr, Ni, Co, Cu, Zn, Zr, Nb, Mo, Sn, Ta, W, Sb, and La.

[0033] Preferably, in step S4, the ionic conductor includes at least one of LATP, LAGP, and LLTO.

[0034] Preferably, in step S4, the organic solution includes an organic solvent and water, and the organic solvent includes at least one of alcohol solvents, ester solvents, ketone solvents, and amide solvents.

[0035] Preferably, in step S4, the ratio of the total molar amount of manganese and iron in the precursor to the molar amount of dopant element M in the dopant conforms to N. Mn+Fe :NM = (0.85-0.98): (0.15-0.02), N Mn+Fe N M These are the total molar amounts of manganese and iron in the precursor and the molar amounts of dopant element M in the dopant, respectively.

[0036] Preferably, in step S4, the ratio of the total molar amount of metal elements in the precursor and dopant to the molar amount of lithium elements in the lithium source conforms to N. Mn+Fe+M :N Li =1: (1.0-1.10), N Mn+Fe+M N Li These are the total molar amount of metal elements in the precursor and dopant, and the molar amount of lithium elements in the lithium source, respectively.

[0037] Preferably, in step S4, the ratio of the total molar amount of metal elements in the precursor and dopant to the total molar amount of phosphorus elements in the precursor and phosphorus source conforms to N Mn+Fe+M :N P =1: (1.0-1.10), N Mn+Fe+M N P These are the total molar amounts of metal elements in the precursor and dopant, and the total molar amounts of phosphorus elements in the precursor and phosphorus source, respectively.

[0038] Preferably, in step S4, the content of the ion conductor is 0.2%-1.5% and the content of carbon is 1%-3.0% based on the mass percentage of the positive electrode active material.

[0039] Preferably, the ionic conductor is LATP, with the chemical formula Li. 1+a Al a Ti 2-a-b N1 b (PO4)3, wherein 0≤a≤0.5, 0≤b≤0.5, and the N1 includes at least one of Zn, Mg, Mn, Co, Ni, Cr, Sc, In, Fe, Y, V, Nb, Ta, Sb, W, Mo, Ru, Ga, Ba, As, Hf, Ge, and Sn.

[0040] Preferably, in step S4, the pre-sintering temperature is 200-500℃, the pre-sintering time is 2-24 hours, and the heating rate is 2-10℃ / min.

[0041] Preferably, in step S4, the high-temperature sintering temperature is 500-900℃, the high-temperature sintering time is 2-24 hours, and the heating rate is 2-10℃ / min.

[0042] Secondly, the present invention provides a positive electrode active material comprising a lithium manganese iron phosphate core and a conductive coating layer disposed on the surface of the lithium manganese iron phosphate core.

[0043] Preferably, the lithium manganese iron phosphate core conforms to the chemical formula LiMn x Fe y M 1-x-y PO4, wherein M is at least one of Mg, Al, Ca, Ti, V, Cr, Ni, Co, Cu, Zn, Zr, Nb, Mo, Sn, Ta, W, Sb, and La, and x and y satisfy 0 < x < 1, 0 < y < 1, and 0 ≤ 1 - xy ≤ 0.2.

[0044] Preferably, the average particle size of the lithium manganese iron phosphate core is 0.5-20 μm, for example, it can be one or any two of the following values: 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm.

[0045] Preferably, the thickness of the conductive coating layer is 2-100 nm, for example, it can be one or any two of the following values: 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, and 100 nm.

[0046] Thirdly, the present invention provides a positive electrode sheet, comprising a positive current collector and a positive active layer disposed on at least one side of the positive current collector, wherein the positive active layer comprises the positive active material, conductive agent and binder as described above.

[0047] Fourthly, the present invention provides a lithium-ion battery, including the positive electrode sheet as described above.

[0048] Compared with the prior art, the beneficial effects of the present invention are as follows: The positive electrode active material of this invention comprises a lithium manganese iron phosphate core and a conductive coating layer. The lithium manganese iron phosphate core is obtained by converting a lithium manganese iron phosphate precursor with a three-layer structure consisting of an oxalate core, a carbonate intermediate layer, and a phosphate shell. The iron and manganese elements in the precursor exhibit a gradient distribution. By controlling the structure and elemental composition of the lithium manganese iron phosphate precursor, the obtained positive electrode active material exhibits characteristics of dense packing, few pores, and high compaction density. Furthermore, it enables the positive electrode active material to form a three-dimensional interconnected transport network, accelerating lithium-ion diffusion and migration, reducing impedance, and improving high-rate discharge performance, thus enhancing the battery's initial cycle efficiency and cycle stability. In addition, through the structural design of a high-manganese core with a high concentration gradient and an iron-rich shell in the precursor, the positive electrode material achieves the effect of a high-capacity high-manganese core and a stable iron-rich shell structure, effectively suppressing manganese dissolution and structural distortion, further improving cycle stability. Attached Figure Description

[0049] Figure 1 The images show SEM images of the positive electrode active material provided in Example 1 of this invention at magnifications of 5.00 KX (left) and 20.00 KX (right).

[0050] Figure 2 This is a charge-discharge curve of the positive electrode active material provided in Embodiment 1 of the present invention.

[0051] Figure 3 The above are charge-discharge curves of the positive electrode active material provided in Example 1 of this invention at different rates. Detailed Implementation

[0052] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available reagents and materials.

[0053] Example 1 One embodiment of the positive electrode active material of the present invention includes a lithium manganese iron phosphate core and a conductive coating layer disposed on the surface of the lithium manganese iron phosphate core; wherein the lithium manganese iron phosphate core is LiMn. 0.54 Fe 0.36 Zr 0.05 La 0.05 PO4; The preparation method of the positive electrode active material described in this embodiment is as follows: Solution preparation: A solution A1 with a total metal ion concentration of 2 mol / L was prepared using 4.5 mol manganese sulfate and 0.5 mol ferrous sulfate, wherein the molar ratio of Mn:Fe = 9:1; A solution A2 with a total metal ion concentration of 2 mol / L was prepared using 7 mol manganese sulfate and 3 mol ferrous sulfate, wherein the molar ratio of Mn:Fe = 7:3; A solution A3 with a total metal ion concentration of 2 mol / L was prepared using 0.5 mol manganese sulfate and 4.5 mol ferrous sulfate, wherein the molar ratio of Mn:Fe = 1:9; Prepare a solution B with an oxalic acid concentration of 2 mol / L by taking 5 mol of oxalic acid; Prepare a solution C with an ammonium bicarbonate concentration of 2 mol / L by taking 10 mol of ammonium bicarbonate; Prepare a solution D with an ammonium dihydrogen phosphate concentration of 2 mol / L by taking 5 mol of ammonium dihydrogen phosphate; Prepare an acid solution with a citric acid concentration of 4 mol / L by taking 20 mol of citric acid; Prepare an alkaline solution with a sodium hydroxide concentration of 4 mol / L by taking 20 mol of sodium hydroxide.

[0054] S1. Add pure water to the reaction vessel, introduce nitrogen gas to purge air, and maintain a nitrogen atmosphere in the vessel; add solution A1, solution B and alkali solution to the reaction vessel simultaneously in parallel, and control the pH of the reaction to be maintained between 2.5±0.2 by adjusting the feed rate of alkali solution. After solution A1 is added, stop feeding and age for 1 hour to obtain a system containing oxalate crystal nuclei. S2. Solution A2, solution C and acid are simultaneously added to the reaction vessel in parallel. The pH of the reaction is controlled to be maintained between 5.0 and 0.2 by adjusting the feed rate of the acid. After solution A2 is added, the feed is stopped and the mixture is aged for 1 hour to obtain a system containing oxalate crystal nuclei coated with carbonate. S3. Solution A3, solution D and alkali solution are simultaneously added to the reaction vessel in parallel. The pH of the reaction is maintained between 6.5 and 0.2 by adjusting the feed rate of alkali solution. After solution A3 is added, the feed is stopped and the mixture is aged for 12 hours. The slurry is washed and filtered multiple times and then dried in a vacuum drying oven at 100°C for 12 hours to obtain a precursor with a three-layer structure, including an oxalate core, a carbonate intermediate layer set on the surface of the oxalate core, and a phosphate shell layer set on the outer surface of the carbonate intermediate layer. S4. 2850.00g of precursor, 754.77g of lithium carbonate, 1773.50g of ammonium dihydrogen phosphate, 136.97g of zirconium oxide, 181.82g of lanthanum oxide, and a composite carbon source (containing 251.52g of anhydrous glucose, 52.20g of PEG, and 14.23g of graphene, with a carbon content ratio of anhydrous glucose:PEG:graphene = 7:2:1) and 31.41g of the ionic conductor LATP (Li 1.3 Al 0.3 Ti 1.7(PO4)3) is uniformly dispersed in 8L of an aqueous solution containing 1mol / L ethylene glycol. After drying, it is placed in a graphite crucible and then placed in a box furnace. Under nitrogen atmosphere protection, the temperature is increased from room temperature to 350℃ at a rate of 5℃ / min, and pre-sintered for 6h. Then, the temperature is increased to 700℃ at a rate of 2℃ / min, and high-temperature sintering is carried out for 12h to obtain the positive electrode active material, including a lithium manganese iron phosphate core and a conductive coating layer on the surface. In the core of lithium manganese iron phosphate: The molar ratio of doping elements conforms to (Mn+Fe):Zr:La=0.9:0.05:0.05, the molar ratio of lithium is (Mn+Fe+Ti+La):Li=1.0:1.02, the molar ratio of phosphorus conforms to (Mn+Fe+Ti+La):P=1.0:1.02, the mass percentage of ionic conductor is 1%, and the mass percentage of carbon is 1.8%.

[0055] Examples 2-7 The only difference between Examples 2-7 and Example 1 is that, during the preparation process, solutions A1, A2, and A3 with different Mn and Fe contents were obtained by adjusting the amount of manganese sulfate and ferrous sulfate, and the amounts of oxalic acid, ammonium bicarbonate, and ammonium dihydrogen phosphate in solutions B, C, and D were adjusted accordingly. This resulted in the preparation of three-layer precursors with different manganese and iron concentration gradients, and the core of the positive electrode active material formed had different Mn and Fe gradients.

[0056] The parameters of solutions A1-A3 in Examples 1-7 and the comparison of the proportions of manganese and iron in the multilayer precursors are shown in Table 1 below.

[0057] Table 1 Example 8 The only difference between Example 8 and Example 1 is that in step S4, no pre-sintering is performed. Instead, the temperature is directly increased from room temperature to 700°C at a rate of 2°C / min under nitrogen atmosphere protection, and sintered for 12 hours to obtain the positive electrode active material.

[0058] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that 3 mol of manganese sulfate and 2 mol of ferrous sulfate were prepared into a solution A1 with a total metal ion concentration of 2 mol / L, 6 mol of manganese sulfate and 4 mol of ferrous sulfate were prepared into a solution A2 with a total metal ion concentration of 2 mol / L, and 3 mol of manganese sulfate and 2 mol of ferrous sulfate were prepared into a solution A3 with a total metal ion concentration of 2 mol / L. This ensures that the molar ratio of metal elements in the three-layer precursor is maintained at Mn:Fe = 6:4, but no concentration gradient is formed.

[0059] Comparative Example 2 Compared with Example 1, the precursor structure of the positive electrode active material in Comparative Example 2 was replaced with oxalate as the core, phosphate as the intermediate layer, and carbonate as the shell. The preparation steps are as follows: (1) Prepare 10 mol of ammonium dihydrogen phosphate into a solution C with an ammonium dihydrogen phosphate concentration of 2 mol / L, prepare 5 mol of ammonium bicarbonate into a solution D with an ammonium bicarbonate concentration of 2 mol / L, and prepare the remaining solutions A1, A2, A3, B, acid solution and alkali solution in the same way as in Example 1. (2) Add pure water to the reaction vessel, introduce nitrogen gas to remove air, and maintain a nitrogen atmosphere in the vessel; add solution A1, solution B and alkali solution to the reaction vessel simultaneously and in parallel, and control the pH of the reaction to be maintained between 2.5 and 0.2 by adjusting the feed rate of alkali solution. After solution A1 is added, stop feeding and age for 1 hour to obtain oxalate crystal nuclei. (3) Add solution A2, solution C and alkali solution to the above reaction vessel simultaneously and in parallel. Control the pH of the reaction to be maintained between 6.5±0.2 by adjusting the feed rate of alkali solution. After solution A2 is added, stop feeding and age for 1 hour to obtain phosphate-coated oxalate crystal nuclei. (4) Solution A3, solution D and acid were added to the above reaction vessel simultaneously and in parallel. The pH of the reaction was maintained between 6.5 and 0.2 by adjusting the feed rate of the acid. After solution A3 was added, the feed was stopped and the mixture was aged overnight. The slurry was washed and filtered multiple times and then dried in a vacuum drying oven at 100°C for 12 h to obtain a three-layer precursor with a molar ratio of Mn to Fe of 6:4. (5) The positive electrode active material was prepared according to the conditions of S4 in Example 1.

[0060] Comparative Example 3 Compared with Example 1, the precursor structure of the positive electrode active material in Comparative Example 3 was replaced with a phosphate core, a carbonate intermediate layer, and an oxalate shell. The preparation steps are as follows: (1) Prepare 5 mol of ammonium dihydrogen phosphate into a solution B with an ammonium dihydrogen phosphate concentration of 2 mol / L, prepare 5 mol of oxalic acid into a solution D with an oxalic acid concentration of 2 mol / L, and prepare the remaining solutions A1, A2, A3, C, acid solution and alkali solution in the same way as in Example 1; (2) Add pure water to the reaction vessel, introduce nitrogen gas to remove air, and maintain a nitrogen atmosphere in the vessel; add solution A1, solution B and alkaline solution to the reaction vessel simultaneously and in parallel, and control the pH of the reaction to be maintained between 6.5±0.2 by adjusting the feed rate of alkaline solution. After solution A1 is added, stop feeding and age for 1 hour to obtain phosphate crystal nuclei. (3) Add solution A2, solution C and acid solution to the above reaction vessel simultaneously and in parallel. Control the pH of the reaction to be maintained between 6.5±0.2 by adjusting the feed rate of acid solution. After solution A2 is added, stop feeding and age for 1 hour to obtain carbonate-coated phosphate crystal nuclei. (4) Solution A3, solution D and alkali solution are added to the above reaction vessel simultaneously and in parallel. The pH of the reaction is controlled to be maintained between 6.5±0.2 by adjusting the feed rate of alkali solution. After solution A3 is added, the feed is stopped and the mixture is aged overnight. The slurry is washed and filtered multiple times and then dried in a vacuum drying oven at 100°C for 12 h to obtain a three-layer precursor with a molar ratio of Mn to Fe of 6:4. (5) The positive electrode active material was prepared according to the conditions of S4 in Example 1.

[0061] Comparative Example 4 Compared with Example 1, the precursor structure of the positive electrode active material in Comparative Example 4 was replaced with a core of carbonate, an intermediate layer of oxalate, and a shell of phosphate. The preparation steps are as follows: (1) Prepare 5 mol of ammonium bicarbonate into solution B with an ammonium bicarbonate concentration of 2 mol / L, and prepare 10 mol of oxalic acid into solution C with an oxalic acid concentration of 2 mol / L; the preparation of the remaining solutions A1, A2, A3, D, acid solution and alkali solution is the same as in Example 1; (2) Add pure water to the reaction vessel, introduce nitrogen gas to remove air, and maintain a nitrogen atmosphere in the vessel; add solution A1, solution B and alkaline solution to the reaction vessel simultaneously and in parallel, and control the pH of the reaction to be maintained between 5.0±0.2 by adjusting the feed rate of alkaline solution. After solution A1 is added, stop feeding and age for 1 hour to obtain carbonate crystal nuclei. (3) Add solution A2, solution C and acid solution to the above reaction vessel simultaneously and in parallel. Control the pH of the reaction to be maintained between 5.0±0.2 by adjusting the feed rate of acid solution. After solution A2 is added, stop feeding and age for 1 hour to obtain oxalate-coated carbonate crystal nuclei. (4) Solution A3, solution D and alkali solution are added to the above reaction vessel simultaneously and in parallel. The pH of the reaction is controlled to be maintained between 6.5±0.2 by adjusting the feed rate of alkali solution. After solution A3 is added, the feed is stopped and the mixture is aged overnight. The slurry is washed and filtered multiple times and then dried in a vacuum drying oven at 100°C for 12 h to obtain a three-layer precursor with a molar ratio of Mn to Fe of 6:4. (5) The positive electrode active material was prepared according to the conditions of S4 in Example 1.

[0062] Comparative Example 5 Compared with Example 1, the precursor structure of the positive electrode active material in Comparative Example 5 was replaced with oxalate as the core, carbonate as the intermediate layer and shell, and the preparation steps are as follows: (1) Prepare a solution D with an ammonium bicarbonate concentration of 2 mol / L by dissolving 5 mol of ammonium bicarbonate; the other solutions A1, A2, A3, B, C, acid solution and alkali solution are prepared in the same way as in Example 1; (2) Add pure water to the reaction vessel, introduce nitrogen gas to remove air, and maintain a nitrogen atmosphere in the vessel; add solution A1, solution B and alkali solution to the reaction vessel simultaneously and in parallel, and control the pH of the reaction to be maintained between 2.5±0.2 by adjusting the feed rate of alkali solution. After solution A1 is added, stop feeding and age for 1 hour to obtain oxalate crystal nuclei. (3) Add solution A2, solution C and acid solution to the reaction vessel simultaneously and in parallel. Control the pH of the reaction to be maintained between 5.0±0.2 by adjusting the feed rate of acid solution. After solution A2 is added, stop feeding and age for 1 hour to obtain carbonate-coated oxalate crystal nuclei. (4) Solution A3, solution D and acid were added to the above reaction vessel simultaneously and in parallel. The pH of the reaction was maintained between 5.0 and 0.2 by adjusting the feed rate of the acid. After solution A3 was added, the feed was stopped and the mixture was aged overnight. The slurry was washed and filtered multiple times and then dried in a vacuum drying oven at 100°C for 12 h to obtain a three-layer precursor with a molar ratio of Mn to Fe of 6:4. (5) Take 2850.00g of the three-layer precursor obtained in (4), 754.77g of lithium carbonate, 2349.92g of ammonium dihydrogen phosphate, 136.97g of zirconium oxide, 181.82g of lanthanum oxide, a composite carbon source (containing 251.52g of anhydrous glucose, 52.20g of PEG, and 14.23g of graphene, wherein the carbon content ratio is anhydrous glucose:PEG:graphene = 7:2:1), and 31.41g of the ion conductor LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) was uniformly dispersed in 8 L of 1 mol / L ethylene glycol solution, and the subsequent steps were carried out by sintering under the conditions of Example 1 to obtain the positive electrode active material.

[0063] Comparative Example 6 Compared with Example 1, the precursor structure of the positive electrode active material in Comparative Example 6 was replaced with oxalate as the core and intermediate layer, and phosphate as the shell. The preparation steps are as follows: (1) Prepare 10 mol of oxalic acid into a 2 mol / L solution C. Prepare the remaining solutions A1, A2, A3, B, D, acid solution and alkali solution in the same way as in Example 1. (2) Add pure water to the reaction vessel, introduce nitrogen gas to remove air, and maintain a nitrogen atmosphere in the vessel; add solution A1, solution B and alkali solution to the reaction vessel simultaneously and in parallel, and control the pH of the reaction to be maintained between 2.5±0.2 by adjusting the feed rate of alkali solution. After solution A1 is added, stop feeding and age for 1 hour to obtain oxalate crystal nuclei. (3) Add solution A2, solution C and acid solution to the above reaction vessel simultaneously and in parallel. Control the pH of the reaction to be maintained between 2.5±0.2 by adjusting the feed rate of acid solution. After solution A2 is added, stop feeding and age for 1 hour to obtain double-layer oxalate crystal nuclei (oxalate-coated oxalate crystal nuclei). (4) Solution A3, solution D and alkali solution are added to the above reaction vessel simultaneously and in parallel. The pH of the reaction is controlled to be maintained between 5.0±0.2 by adjusting the feed rate of alkali solution. After solution A3 is added, the feed is stopped and the mixture is aged overnight. The slurry is washed and filtered multiple times and then dried in a vacuum drying oven at 100℃ for 12 h to obtain a three-layer precursor with a molar ratio of Mn to Fe of 6:4. (5) The positive electrode active material was prepared according to the conditions of S4 in Example 1.

[0064] Comparative Example 7 Compared with Example 1, the precursor structure of the positive electrode active material in Comparative Example 7 was replaced with a core and intermediate layer of carbonate and a shell of phosphate. The preparation steps are as follows: (1) Prepare 5 mol of ammonium bicarbonate into solution B with an ammonium bicarbonate concentration of 2 mol / L. Prepare the remaining solutions A1, A2, A3, C, D, acid solution and alkali solution in the same way as in Example 1. (2) Add pure water to the reaction vessel, introduce nitrogen gas to remove air, and maintain a nitrogen atmosphere in the vessel; add solution A1, solution B and alkaline solution to the reaction vessel simultaneously and in parallel, and control the pH of the reaction to be maintained between 5.0±0.2 by adjusting the feed rate of alkaline solution. After solution A1 is added, stop feeding and age for 1 hour to obtain carbonate crystal nuclei. (3) Add solution A2, solution C and acid solution to the above reaction vessel simultaneously and in parallel. Control the pH of the reaction to be maintained between 2.5±0.2 by adjusting the feed rate of acid solution. After solution A2 is added, stop feeding and age for 1 hour to obtain double-layer carbonate crystal nuclei (carbonate-coated carbonate crystal nuclei). (4) Solution A3, solution D and alkali solution are added to the above reaction vessel simultaneously and in parallel. The pH of the reaction is controlled to be maintained between 5.0±0.2 by adjusting the feed rate of alkali solution. After solution A3 is added, the feed is stopped and the mixture is aged overnight. The slurry is washed and filtered multiple times and then dried in a vacuum drying oven at 100℃ for 12 h to obtain a three-layer precursor with a molar ratio of Mn to Fe of 6:4. (5) The positive electrode active material was prepared according to the conditions in S4 of Example 1. To investigate the application effect of the positive electrode active material provided by the present invention in batteries, the following tests were conducted: 1.1 The microstructure and particle size of the materials in the examples were characterized by scanning electron microscopy (SEM); 2. The compaction density of the material was tested using a PRCD3100 powder resistivity and compaction density meter; 3. The prepared positive electrode active material, conductive carbon black (SP) as the conductive agent, and polyvinylidene fluoride (PVDF) as the binder were weighed at a mass ratio of 8:1:1. Using N-methylpyrrolidone (NMP) as the solvent, the mixture was ball-milled in a planetary ball mill for 2 hours to prepare a positive electrode slurry. This slurry was then coated onto an aluminum foil current collector, dried, and then rolled and punched into a positive electrode sheet. The sheet was then dried in a vacuum drying oven for 12 hours, and finally placed in a glove box under an inert gas protective atmosphere. The negative electrode used a lithium metal sheet. The electrolyte was a 1M LiPF6 / ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) mixed solution, with a volume ratio of EC, DMC, and DEC of 1:1:1. The separator was a polypropylene microporous membrane, Celgard 2300. The resulting assembly was a CR2032 coin cell. Subsequently, under conditions of 25℃±2℃, the assembled button lithium-ion batteries were placed on a battery testing system (Blue Electric series battery testing system) for charge-discharge cycle testing. The test conditions were as follows: charge-discharge rates of 0.1C, 1C, and 8C, voltage range of 2.5V-4.3V, with one charge and one discharge cycle constituting one cycle. The conductivity, charge specific capacity, discharge specific capacity, first charge-discharge efficiency (i.e., first-cycle coulombic efficiency), and capacity retention rate after 500 cycles were recorded.

[0065] The compaction density, discharge specific capacity at 0.1C, discharge specific capacity at 8C, and capacity retention rate after 500 cycles at 1C for each embodiment and comparative example are shown in Table 2; the charge-discharge curves are shown in the figure. Figure 2 The charge-discharge curves at different rates are as follows: Figure 3 .

[0066] Table 2 Combination Figure 1 , Figure 2, Figure 3 As can be observed from Table 2: Compared with Comparative Examples 1-7, the compaction density of the positive electrode active material in Examples 1-8 is improved to a certain extent, and the discharge capacity and capacity retention rate of the battery at discharge rates of 0.1C and 8C are significantly better than those of Comparative Examples 1-7.

[0067] SEM image of the positive electrode active material in Example 1 is shown below. Figure 1 As can be seen, the positive electrode active material is a regular spherical secondary particle composed of primary particles combined, and the primary grains on the surface of the positive electrode active material are tightly packed and have good density. It includes a lithium manganese iron phosphate core and a conductive carbon coating layer, with a particle size in the range of 0.5-20μm.

[0068] Compared to Example 1, although a multi-layer precursor structure was also formed in Comparative Example 1, the spatial gradient regulation of Mn and Fe was not achieved, resulting in a significant decrease in the 8C discharge specific capacity and cycle capacity retention of the prepared lithium-ion battery. In Comparative Examples 2-7, when the types of deposited salts selected for each layer of the precursor were unsuitable, the superior performance of the cathode active material of this invention could not be achieved. Furthermore, as can be seen from Examples 1-8, the molar ratio of the components in each layer of the precursor, the changes in the Mn / Fe gradient, and the conditions of the two-step sintering process also have a certain impact on the performance of the cathode active material when applied to the battery.

[0069] In summary, this invention utilizes a precursor with a specific three-layer deposition junction and a concentration gradient distribution of Fe and Mn to prepare the positive electrode active material, resulting in electrical properties such as high compaction, high rate capability, and long lifespan. Furthermore, through its unique three-layer precursor design and preparation process, this invention significantly improves the ion or electron migration efficiency in the positive electrode active material and enhances crystal structure stability, thereby improving the rate performance and stability of lithium-ion batteries, demonstrating significant application value.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a positive electrode active material, characterized in that, Includes the following steps: S1. Under an inert gas atmosphere, oxalic acid source and solution A1 are reacted at pH-1 to obtain a system containing oxalate crystal nuclei. S2. Maintaining an inert gas atmosphere, add solution A2 and a carbonic acid source to the system containing oxalate crystal nuclei, and react at pH-2 to obtain a system containing carbonate-coated oxalate crystal nuclei. S3. Maintaining an inert gas atmosphere, add solution A3 and a phosphoric acid source to the system containing carbonate-coated oxalate crystal nuclei, and react at pH-3. After solid-liquid separation, washing, and drying, a solid precursor is obtained. The precursor comprises an oxalate core, a carbonate intermediate layer disposed on the surface of the oxalate core, and a phosphate shell disposed on the outer surface of the carbonate intermediate layer; the precursor comprises manganese and iron, and the precursor satisfies the following relationship: M1 > M2 > M3, N1 < N2 < N3, where M1, M2, and M3 are the percentages of the molar amount of manganese in the oxalate core, carbonate intermediate layer, and phosphate shell relative to the total molar amount of manganese and iron, respectively; and N1, N2, and N3 are the percentages of the molar amount of iron in the oxalate core, carbonate intermediate layer, and phosphate shell relative to the total molar amount of manganese and iron, respectively. S4. The precursor, lithium source, phosphorus source, dopant, composite carbon source, ion conductor and organic solution are mixed and then subjected to drying, pre-sintering under an inert atmosphere and high-temperature sintering in sequence to obtain the positive electrode active material. In S1 to S3, solution A1, solution A2 and solution A3 include a manganese source and / or an iron source.

2. The method for preparing the positive electrode active material as described in claim 1, characterized in that, Includes at least one of the following I-VI: I. M1 is 80%-100%; II. The N1 is 0%-20%; III. The M2 mentioned above is 50%-80%; IV. The N2 content is 20%-50%; V. The M3 is 0%-40%; VI. The N3 is 60%-100%.

3. The method for preparing the positive electrode active material as described in claim 1, characterized in that, In the reaction in S1, pH-1 is controlled to be 1-3; And / or, the pH-2 in the reaction of S2 is controlled to be 3-5.5; And / or, the pH-3 in the reaction of S3 is controlled to be 5.5-7.

4. The method for preparing the positive electrode active material as described in claim 1, characterized in that, In S1, the molar ratio of manganese to iron in solution A1 is (7-10):(0-3). And / or, in S2, the molar ratio of manganese to iron in solution A2 is (3-7):(3-7). And / or, in S3, the molar ratio of manganese to iron in solution A3 is (0-3):(7-10).

5. The method for preparing the positive electrode active material as described in claim 1, characterized in that, In step S4, the composite carbon source includes at least two of the following: sucrose, glucose, citric acid, fructose, starch, maltose, cellulose, dextrin, lactose, oxalic acid, polypropylene, polyvinylpyrrolidone, polyethylene glycol, carbon black, carbon nanotubes, and graphene. And / or, in S4, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate; And / or, in S4, the phosphorus source includes at least one of phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate; And / or, in S4, the dopant includes at least one of oxides, oxalates, and carbonates of M, wherein M is at least one of Mg, Al, Ca, Ti, V, Cr, Ni, Co, Cu, Zn, Zr, Nb, Mo, Sn, Ta, W, Sb, and La; And / or, in S4, the ionic conductor includes at least one of LATP, LAGP, and LLTO; And / or, in S4, the organic solution includes an organic solvent and water, and the organic solvent includes at least one of alcohol solvents, ester solvents, ketone solvents, and amide solvents.

6. The method for preparing the positive electrode active material as described in claim 1, characterized in that, In step S4, the pre-sintering temperature is 200-500℃, the pre-sintering time is 2-24 hours, and the heating rate is 2-10℃ / min. And / or, in S4, the high-temperature sintering temperature is 500-900℃, the high-temperature sintering time is 2-24 hours, and the heating rate is 2-10℃ / min.

Citation Information

Patent Citations

  • Ferromanganese oxalate precursor, lithium manganese iron phosphate material, and preparation methods and applications of manganese iron oxalate precursor and lithium manganese iron phosphate material

    CN121226152A